The unloved dollar standard from Bretton Woods to the rise of China - McKinnon, Ronald I. (New York : Oxford University Press, 2013)
This study argues that rehabilitating the dollar standard requires that American monetary and financial policies be 'internationalized': the Federal Reserve should aim for greater exchange rate stability by adjusting interest rates to prevent runs for or against the dollar, while the U.S. Treasury aims fiscal policy to balance exports and imports. China, now the world's largest exporter and creditor country, has a critical role to play in sustaining the dollar standard.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Foreign exchange; Dollar, American; Money -- United States; Money -- China; Currency question; Currency convertibility